Teenagers’ percept ion about sexually transmitt ed diseases and contraception - Garbin, Cléa A.S.; Lima, Daniela Pereira; Dossi, Ana Paula; Arcieri, Renato M.; Rovida, Tânia A.S. (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: sexually transmitted diseases (DST) can represent an important impact on teenager’s health due its consequences. Objective: to identify the perception and knowledge of teenagers about DST, its transmission forms and contraception. Methods: it was made a cross-sectional study type investigation, with 136 teenager students from a Technical Education Public Institution in a middle-sized city. It was used a tested instrument, self answered, with opened and closed questions about theme and sociodemographic data. The same data were stored and analyzed by Program Epi Info version 3.5.1. Results: 97,1% affirmed to know male condoms, 89,0% oral contraceptives, 87,5% female condoms, 74,3% postcoital contraceptives, 47,8% natural family planning methods, 41,9% hormonal injection, 33,1% intrauterine devices, 31,6% coitus interruptus and 1,5% other contraceptive methods. According with them, the information was gave principally on high school (46,1%), by friends or partners (20,3%), doctor (10,9%), television (10,2%). In relation to DST, 98,5% affirmed that diseases can be transmitted during coitus. The aids (91,2%) and herpes (72,8%) were the most cited diseases. Just 31,6% of teenagers affirmed that run the risk to acquire some DST, and 88,4% of them, due no use of condoms, 30,2% due their partner make relation with other people, 18% due have many sexual partners and 9,3% due other causes. Conclusion: even teenagers knowing many contraceptive methods and sexually transmitted diseases, the teenagers have not prevented theirselves yet. It’s necessary that the high school reinforce the use of contraceptive methods, because the school is an important source of educative information on health area.